THE ISSUES OF DEVELOPING PROFESSIONAL COMMUNICATIVE COMPETENCE OF MEDICAL STUDENTS IN A FOREIGN LANGUAGE (Scientific journal of the Fergana State University, 2023)
The article studied the problems and solutions for developing communicative competence of medical students in a foreign language. The article also explored the research works of linguists on developing communicative competence in foreign languages. The terms “competence” and “competent specialist” have been defined.